ARBITRATION AND JUSTICE DENIAL ON FOREIGN DIRECT INVESTMENT - Hendrawan, Daniel (UI Scholars Hub, 2016)
The economic growth in Indonesia is thrive. The Economic growth can not be separate of the role of investment in Indonesia. The population in Indonesia very much and also the location of the Indonesian state strategic pretty much made Indonesia enjoyed by citizens of Indonesia itself and also foreign nationals who wish to also invest in Indonesia. In Indonesia there is a domestic investment and foreign investment. In this paper will be devoted to foreign investment. Foreign investment that currently exist in Indonesia has a sizeable amount and spread from Sabang to Merauke, and also has a fairly diverse business fields. The investors who come in and make an investment in Indonesia is sometimes caused the dispute. Dispute occurs either the foreign investment by government or also foreign investment with other parties outside the government well with other foreign investment, and also in the company itself. Foreign investment dispute settlement is not only done through the court owned by the government, but there are also ways of alternative dispute resolution outside the court . One of the alternative dispute resolution outside the court is Arbitration. Arbitration carried out as part of efforts to achieve settlement of the problem in terms of investment activity . Arbitration itself is set in the legislation applicable investment in Indonesia . The parties in capital investment may create a separate section in the agreement governing the settlement of disputes in the case of investments completed by Arbitration. In the event that the parties have arranged to settle the case with Arbitration, then the court is not allowed to try again or to interfere in the decision Arbitration. Arbitration is one of the solutions if justice denial occur in the settlement of foreign direct investment issue.